Second-Best Renewable Subsidies to De-Carbonize the Economy: Commitment and the Green Paradox - Armon Rezai; Frederick Van der Ploeg (Center for Economic Studies and ifo Institute (CESifo), 2016)
Climate change must deal with two market failures: global warming and learning by doing in renewable use. The first-best policy consists of an aggressive renewables subsidy in the near term and a gradually rising and falling carbon tax. Given that global carbon taxes remain elusive, policy makers have to use a second-best subsidy. In case of credible commitment, the second-best subsidy is set higher than the social benefit of learning. It allows the transition time and peak warming close to first-best levels at the cost of higher fossil fuel use (weak Green Paradox). If policy makers cannot commit, the second-best subsidy is set to the social benefit of learning. It generates smaller weak Green Paradox effects, but the transition to the carbon-free takes longer and cumulative carbon emissions are higher. Under first-best and second best with pre-commitment peak warming is 2.1 - 2.3 °C, under second best without commitment 3.5°C, and without any policy temperature 5.1°C above pre-industrial levels. Not being able to commit yields a welfare loss of 95% of initial GDP compared to first best. Being able to commit brings this figure down to 7%.
Keywords: H21; Q51; Q54; 330; first-best and second-best policy; commitment; Markov-perfect; Ramsey growth; carbon tax; renewables subsidy; learning by doing; directed technical change